Baseline characteristics of patients in the Reduction of Events with Darbepoetin alfa in Heart Failure trial (RED‐HF). (March 2013) - McMurray, John J.V.; Anand, Inder S.; Diaz, Rafael; Maggioni, Aldo P.; O'Connor, Christopher; Pfeffer, Marc A.; Solomon, Scott D.; Tendera, Michal; van, Dirk J.; Albizem, Moetaz; Cheng, Sunfa; Scarlata, Debra; et al.
<x xml:space="preserve">Abstract</x> Aims This report describes the baseline characteristics of patients in the Reduction of Events with Darbepoetin alfa in Heart Failure trial (RED‐HF) which is testing the hypothesis that anaemia correction with darbepoetin alfa will reduce the composite endpoint of death from any cause or hospital admission for worsening heart failure, and improve other outcomes. Methods and results Key demographic, clinical, and laboratory findings, along with baseline treatment, are reported and compared with those of patients in other recent clinical trials in heart failure. Compared with other recent trials, RED‐HF enrolled more elderly [mean age 70 (SD 11.4) years], female (41%), and black (9%) patients. RED‐HF patients more often had diabetes (46%) and renal impairment (72% had an estimated glomerular filtration rate <60 mL/min/1.73 m2). Patients in RED‐HF had heart failure of longer duration [5.3 (5.4) years], worse NYHA class (35% II, 63% III, and 2% IV), and more signs of congestion. Mean EF was 30% (6.8%). RED‐HF patients were well treated at randomization, and pharmacological therapy at baseline was broadly similar to that of other recent trials, taking account of study‐specific inclusion/exclusion criteria. Median (interquartile range) haemoglobin at baseline was 112 (106–117) g/L. Conclusion The anaemic patients enrolled in RED‐HF were older, moderately to markedly symptomatic, and had extensive co‐morbidity.